EFFECTIVENESS OF CLINICAL RISK MANAGEMENT IN INTENSIVE CARE - Ruy de Almeida Barcellos; Melise Toscan; Ana Cristina Pretto Báo; Simone Coelho Amestoy (Universidade Federal do Paraná, 2016)
The present study aimed to measure the effectiveness of clinical risk management in intensive care. Cross-sectional study with quantitative approach conducted in a philanthropic hospital in the city of Caxias do Sul. The sample was composed of patients admitted to the intensive care unit included in the risk management assessment form in the period of January 2013 to December 2014. The risks analyzed in this study were fall; skin lesion; unplanned extubation; accidental removal of nasoenteral feeding tube and nasogastric tube and accidental catheter removal for central venous catheter. The sample was composed of 51,220 patients-day. According to the results obtained, the effectiveness of the management of the risks investigated in this study was above 99%. It is concluded that nursing plays a key role in risk management, an activity that requires continuing training of nurses, with focus on care quality and safety.